Visual Field and Optical Coherence Tomography Parameters With and Without Positive Family History of Glaucoma - Bhatta, Sabitri; Awasthi, Suresh; Basnet, Gyan Bahadur; Maharjan, Indra Man (Journal of Nepal Health Research Council, 2024)
Background: To evaluate the Retinal Nerve Fiber Layer and Ganglion Cell Complex thickness using Spectral Domain Optical Coherence Tomography with and without positive family history of Primary Open Angle Glaucoma and its relation to visual field. Methods: Total 120 eyes with each subjects with positive family history of Primary Open Angle Glaucoma (Group I, n=30) and healthy subjects without positive family history of Primary Open Angle Glaucoma (Group II, n=30) undergone complete ophthalmic evaluation with Retinal Nerve Fiber Layer, Ganglion Cell Complex and VF obtained from Spectral Domain Optical Coherence Tomography RTVue-100 and Humphrey visual field respectively .The measurements were analyzed and compared among two groups using independent-t test by using SPSS version 23.The relationship of Retinal Nerve Fiber Layer with visual field were evaluated with correlation analysis. Results: The Intra Ocular Pressure and vertical Cup Disc Ratio were significantly higher in Group I with mean difference of 2.48±0.43 (p<0.001) and 0.18±0.23 (p<0.001) respectively. The average, superior, inferior, nasal, temporal RNFL and average Ganglion Cell Complex was significantly lower and thinner in Group I with mean difference of -8.53±2.30 µm (p<0.001), -7.35±3.34 µm (p<0.001), -8.52±3.58µm (p<0.001),-11.87±2.24µm (p<0.001), -5.31±1.95µm (p<0.001) and -8.05±1.52µm (p<0.001) respectively. Correlation plot with Retinal Nerve Fiber Layer thickness as predictor of Mean Deviation and Pattern Standard Deviation indicated statistically significant degree of determination in Group I (r=0.455 and r=0.623, p<0.001 and p<0.001). Conclusions: The Optical Coherence Tomography and visual field Parameters are lower in group I and used as an early predictor, diagnosis, monitoring and management. Keywords: Family history; first degree relatives; ganglion cell complex; primary open angle glaucoma; retinal nerve fiber layer.